The Role of Store Image on Repurchase Intention with Customer Satisfaction as Mediation - Nimas Anggita Iddo Driantami; Ari Prasetyo (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan untuk mengetahui peran dari store image terhadap repurchase intention pada Karita Muslim Square Surabaya yang di mediasi dengan customer satisfaction. Sampel yang digunakan yaitu 131 responden yang pernah melakukan pembelian di Karita Muslim Square Surabaya. Pengujian menggunakan SEM-PLS dengan konstruk pertama yang menunjukkan hasil yang tidak valid, sehingga pengujian dilanjutkan dengan pengujian konstruk kedua dengan mengeliminasi beberapa indikator, sehingga hasil evaluasi menunjukkan bahwa antar variabel dalam konstruk secara langsung memiliki pengaruh yang positif signifikan. Sedangkan secara tidak langsung customer satisfaction menunjukkan hubungan yang positif signifikan dalam memediasi store image terhadap repurchase intention. Sehingga customer satisfaction memiliki peran partial mediation dalam peneltian ini. Penelitian ini diharapkan memiliki manfaat bagi perusahaan terkait maupun sejenis agar mampu melihat segala peluang yang ada disekitar dengan memanfaatkan setiap komponen maupun dimensi citra toko agar dapat dimanfaatkan secara maksimal untuk mencapai tujuan dari tiap-tiap perusahaan. Kata Kunci: Store Image, Customer satisfaction, Repurchase intention, Islamic Retail. ABSTRACT This study aims to determine the role of store image on repurchase intention at Karita Muslim Square Surabaya which is mediated by customer satisfaction. The sample used is 131 respondents who have purchased at Karita Muslim Square Surabaya. The test uses SEM-PLS with the first construct showing invalid results, so the test is continued with the second construct testing by eliminating several indicators, the evaluation results show that the variables in the construct directly have a significant positive effect. Meanwhile, customer satisfaction indirectly shows a significant positive relationship in mediating store image on repurchase intention. So customer satisfaction has a partial mediation role in this research. This research is expected to have benefits for related and similar companies so they are able to see all the opportunities that exist by utilizing every component and dimension of the store image so they can be utilized optimally to achieve the goals of each company. Keywords: Store Image, Customer satisfaction, Repurchase intention, Islamic retail. DAFTAR PUSTAKA Akter, S., & Ashraf, E. (2016). Factors affecting repurchase intention of customers: In the context of retail chain store industry in Bangladesh. European Journal of Business and Management, 8(32), 40–47. Bray, J. (2008). Consumer behaviour theory: Approaches and models. Unpublished Discussion paper. Retrieved from https://eprints.bournemouth.ac.uk/10107/1/Consumer_Behaviour_Theory_-_Approaches_%26_Models.pdf Burlison, J., & Oe, H. (2018). A discussion framework of store image and patronage: A literature review. International Journal of Retail and Distribution Management, 46(7), 705–724. https://doi.org/10.1108/IJRDM-11-2017-0275 Burt, S., & Carralero-Encinas, J. (2000). The role of store image in retail internationalisation. International Marketing Review, 17(4–5), 433–453. https://doi.org/10.1108/02651330010339941 Cuong, P. H. (2019). Antecedents of store management strategies and visual merchandising on the in-store engagement of consumer good buyers: An empirical study. Global Business and Finance Review, 24(4), 76–89. https://doi.org/10.17549/gbfr.2019.24.4.76 Gocek, I., & Beceren, Y. I. (2012). Assessment of the effects of store image, perceived risk and customer relations on customer satisfaction in the textile industry. International Journal of Business and Social Science, 3(9), 133–146. Hamid, R. S., & Anwar, D. S. M. (2019). Structural equation modeling (SEM) berbasis varian: Konsep dasar dan aplikasi dengan program SmartPLS 3.2.8 dalam riset bisnis. Jakarta: PT. Inkubator Penulis Indonesia. Harahap, L. K. (2020). Analisis SEM (Structural equation modelling) dengan SMARTPLS (Partial least square). Fakultas Sains dan Teknologi UIN Walisongo Semarang, 1, 1-11. Haryono, S. (2017). Metode SEM untuk penelitian manajemen dengan AMOS LISREL PLS. Bekasi: PT. Intermedia Personalia Utama. Hellier, P. K., Geursen, G. M., Carr, R. A., & Rickard, J. A. (2003). Customer repurchase intention. European Journal of Marketing, 37(11/12), 1762–1800. https://doi.org/10.1108/03090560310495456 Ho, H. T., Nguyen, T. K. A., Olsen, S. O., & Vassdal, T. (2010). Explaining repurchase intention towards in Vietnam: The extension of the theory of planned behavior. IIFET 2010 Montpellier Proceedings, 1–12. Hosseini, Z., Jayashree, S., & Malarvizhi, C. (2014). Store image and its effect on customer perception of retail stores. Asian Social Science, 10(21), 223–235. https://doi.org/10.5539/ass.v10n21p223 Ibzan, E., Balarabe, F., & Jakada, B. (2016). Consumer satisfaction and repurchase intentions. Developing Country Studies, 6(2), 96–100. Indrasari, M. (2019). Pemasaran dan kepuasan pelanggan. Surabaya: Unitomo press. Bloemer, J. & Ruyter, K. D. (1997). On the relationship between store image, store satisfaction and store loyalty. European Journal of Marketing, 32(5/6), 499–513. https://doi.org/10.1108/03090569810216118 Kementerian Perencanaan Pembangunan Nasional. (2019). Masterplan Ekonomi syariah Indonesia 2019-2024. Jakarta: Kementerian Perencanaan Pembangunan Nasional. Khoa, B. T., Nguyen, T. D., & Nguyen, V. T. T. (2020). Factors affecting customer relationship and the repurchase intention of designed fashion products. Journal of Distribution Science, 18(2), 17–28. https://doi.org/10.15722/jds.18.2.20202.17 Kotler, P., & Armstrong, G. (2016). Principles of marketing. New York: Pearson Education. Kotler, P., & Keller, K. K. (2012). Marketing management. New York: Pearson Education. Kotler, P., & Keller, K. L. (2009). Manajemen pemasaran. New York: Pearson education. Nurhidayatuloh, & Nugroho, A. P. (2010). Marketing strategy in modern retail business in the sharia economic perspective, 1-27. Richard, L. (1999). Whence consumer loyalty? Journal of Marketing, 63(Special Issue 1999), 33–44. https://doi.org/10.2307/1252099 Setyo, W., & Wibowo, A. (2013). The effect of store image, product signature and product varitation towards repurchase intention in niki eco store Semarang. Journal of Management, 1(1), 1–18. Silva, T. S., & Giraldi, J. de M. E. (2010). The influence of store image on customer satisfaction: a case study of a shoe store. Brazilian Business Review, 7(2), 60–77. https://doi.org/10.15728/bbr.2010.7.2.4 Syifa Johan, I., Indriyani, R., & Vincēviča-Gaile, Z. (2020). Measuring repurchase intention on fashion online shopping. SHS Web of Conferences, 76, 01015. https://doi.org/10.1051/shsconf/20207601015 Tellis, G. J. (1988). Advertising exposure, loyalty, and brand purchase: A two-stage model of choice. Journal of Marketing Research, 25(2), 134-144. https://doi.org/10.2307/3172645 Uğur, Ö. G. (2017). The effects of store image characteristics on repurchase intention and word of mouth marketing: sivas aydinli readymade store example. The Journal of Academic Social Science, 40(2016), 332–343. http://dx.doi.org/10.16992/ASOS.11930 Visser, E. M., Du Preez, R., & Janse Van Noordwyk, H. S. (2006). Importance of apparel store image attributes: Perceptions of female consumers. SA Journal of Industrial Psychology, 32(3). https://doi.org/10.4102/sajip.v32i3.437 Watanabe, E. A. de M., Lima-Filho, D. D. O., & Torres, C. V. (2013). Store image attributes and customer satisfaction in supermarkets in Campo Grande-MS. Revista Brasileira de Marketing, 12(4), 85–107. https://doi.org/10.5585/remark.v12i4.2561 Yalcin, A., Aksoy, L., Keiningham, T. L., Larivière, B., III, F. V. M., & Mithas, S. (2012). The satisfaction, repurchase intention and shareholder value linkage: A longitudinal examination of fixed and firm-specific effects. International Conference on Economic Modeling, Proceedings, 37.